Identifikasi Tumbuhan Spermatophyta di Desa Bulili Kecamatan Lore Selatan sebagai Sumber Belajar Mahasiswa FKIP Biologi Unsimar Poso - Muhdin, Nining Kasim; Frangki, Ngkalao (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2023)
Abstract : This study aims to determine the types of seed plants (spermatophytes) in Bulili Village as a learning resource for FKIP Biology Unsimar students. This study uses an exportative quantitative method. The population in this study were all spermatophyta plants with a tree habit, totaling 1,931 species or trees. The samples used in this study were spermatophyta plants with a tree habit. The sampling technique was carried out using the roaming method. Furthermore, the data were analyzed using printed books. The findings from the research showed that in Bulili village there were 1,491 plant species with 32 species belonging to 21 families. These families are Fabaceae, Maraceae, Oxalidaceae, Bombacaceae, Lauraceae, Arecaceae, Fabaceause, Lamiaceae, Euphorbiaceae, Anacardiaceae, Sapindaceae, Myrtaceae, Combretaceae, Malvaceae, Gnetaceae, Sapotaceae, Caricaceae, Clusiaceae, Meliaceae, Rubiaceae, Ebenaceae which are suitable for use as learning resources for Biology FKIP Unsimar Poso students.